Report of the Council of Management and of the Director for 1964 - Anonymus, A.
British Institute of Archaeology at Ankara; spez. 10: British Urartian Project, 1964; 10-11: D. H. French, Can Hasan, 1964; 13-14: I. A. Todd, Central Anatolian Survey.